CKS1B nuclear expression is inversely correlated with p27Kip1 expression and is predictive of an adverse survival in patients with multiple myeloma - Hong Chang; Nan Jiang; Hua Jiang; Manujendra N. Saha; Connie Qi; Wei Xu; Donna Reece (Haematologica, 2010)
Background CKS1B is a member of the highly conserved cyclin kinase subunit 1 (CKS1) family that interacts with cyclin-dependent kinases and plays an important role in cell cycle progression. We and others have shown that CKS1B amplification located on chromosome 1q21 is an adverse prognostic factor in multiple myeloma, but its relationship with CKS1B nuclear protein expression, is unclear. The aim of this study was to correlate nuclear CKS1B protein immunoreactivity, 1q21 amplification status, p27Kip1 expression and survival in patients with newly-diagnosed multiple myeloma.Design and Methods Nuclear expression of CKS1B and p27Kip1 was evaluated by immunohistochemistry in decalcified, paraffin-embedded bone marrow biopsies from 94 patients with newly diagnosed multiple myeloma. Clonal plasma cells of the bone marrow aspirates from the same cohort were examined for CKS1B gene status by interphase cytoplasmic fluorescence in situ hybridization.Results Fluorescence in situ hybridization detected the 1q21 amplification in 36 (38%) of the 94 patients and immunohistochemistry showed CKS1B protein expression in 37 (39%). Thirty-two (86%) of the 36 amplified (1q21) cases expressed CKS1B and 31 (84%) of the 37 CKS1B immunore-active cases had amplified 1q21. 1q21 amplification and CKS1B protein expression were strongly correlated (P